1986
DOI: 10.1172/jci112533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on glucose-mediated glucose disposal and glucose transport.

Abstract: To assess the effects of aging on glucose-mediated glucose disposal and glucose transport, glucose disposal rates were measured in 10 nonelderly (32±4 yr) and 11 elderly (64±4 yr) subjects at five different plasma glucose concentrations. Glucose disposal was decreased by 30-35% in the elderly at each level ofglycemia (100-350 mg/dl) in the presence of similar levels of hyperinsulinemia (-100 MU/ml), and the 50% effective concentration (EC50) was similar in both the nonelderly (100±9) and elderly (103±5 mg/dl).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 35 publications
6
45
0
Order By: Relevance
“…These results confirm previous observations by Nishimura et al (7), although in our study the differences in glucose disposal rate reach statistical significance, whereas in their study (7) this was the case only at lower insulin concentrations. Additionally, these data are consistent with the findings in elderly humans (3,4,27) who lack genetic commitments to develop noninsulin-dependent diabetes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results confirm previous observations by Nishimura et al (7), although in our study the differences in glucose disposal rate reach statistical significance, whereas in their study (7) this was the case only at lower insulin concentrations. Additionally, these data are consistent with the findings in elderly humans (3,4,27) who lack genetic commitments to develop noninsulin-dependent diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…In this work we have not determined the fat-free mass of the rats, but from the similarity in body weight between the animals in this study and those used previously (7), we can tentatively assume that the fat-free mass amounts to 62% and 55% of body weight in young and old rats, respectively. This would result in glucose disposal rates of 28 and 20 mg/min⅐kg fat-free mass, for young and old rats, respectively, at the highest insulin level, indicating that old animals also show insulin resistance when glucose disposal is calculated on a fat-free mass basis, in agreement to similar findings in humans (27).…”
Section: Euglycemic-hyperinsulinemic Clampsupporting
confidence: 81%
See 1 more Smart Citation
“…It is well established that aging is associated with an increase in insulin resistance accompanied by a decline in glucose tolerance (De Fronzo 1981;Rowe et al 1983;Fink et al 1986). Aging alters body composition, leading to an increase in central fat mass, which contributes to the development of insulin resistance (for a review, see Seals and Bell 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is also associated with changes in body composition, especially in adipose tissue, making it difficult to evaluate the role of ageing by itself in the impairment of insulin action. Thus, while several reports have shown that decreased insulin sensitivity occurs in non-obese elderly humans (Fink et al 1983(Fink et al , 1986, some have concluded that insulin resistance in the elderly derives from changes in body composition due to fat accumulation (Ferrannini et al 1996, Basu et al 2003. In this sense, it has been described that specific removal of epididymal and perirenal fat in 15-month-old F344/Brown Norway rats prevents the development of ageing-associated insulin resistance (Gabriely et al 2002).…”
Section: Introductionmentioning
confidence: 99%